Improving Productivity in Design and Development of Information Technology (IT) Service Delivery Simulation Models. (February 2015) - Beloglazov, Anton; Banerjee, Dipyaman; Hartman, Alan; Buyya, Rajkumar
The unprecedented scale of Information Technology (IT) service delivery requires careful analysis and optimization of service systems. The simulation is an efficient way to handle the complexity of modeling and optimization of real-world service delivery systems. However, typically developed custom simulation models lack standard architectures and limit the reuse of design and implementation artifacts across multiple models. In this work, following the design science research methodology, based on a formal model of service delivery systems and applying an adapted software product line (SPL) approach, we create a design artifact for building product lines of IT service delivery simulation models, which vastly simplify and reduce the cost of simulation model design and development. We evaluate the design artifact by constructing a product line of simulation models for a set of IBM's IT service delivery systems. We validate the proposed approach by comparing the simulation results obtained using our models with the results from the corresponding custom simulation models. The case study demonstrates that the proposed approach leads to 5–8 times reductions in the time required to design and develop related simulation models. The potential implications of the application of the proposed approach within an organization are quicker responses to changes in the business environment, more information to assist in managerial decisions, and reduced workload on the process reengineering specialists.